Targeting Mechanosensitive Piezo1 Alleviated Renal Fibrosis Through p38MAPK-YAP Pathway - Fu, Yuanyuan; Wan, Pengzhi; Zhang, Jie; Li, Xue; Xing, Jia; Zou, Yu; Wang, Kaiyue; Peng, Hui; Zhu, Qizhuo; Cao, Liu; Zhai, Xiaoyue (Frontiers in Cell and Developmental Biology, 2021)
Renal fibrosis is the most common pathological manifestation of a wide variety of chronic kidney disease. Increased extracellular matrix (ECM) secretion and enhanced microenvironment stiffening aggravate the progression of renal fibrosis. However, the related mechanisms remain unclear. Here, we evaluated the mechanism by which ECM stiffness aggravates renal fibrosis. In the present study, renal mesangial cells (MCs) were cultured on polyacrylamide hydrogels with different stiffness accurately detected by atomic force microscopy (AFM), simulating the in vivo growth microenvironment of MCs in normal kidney and renal fibrosis. A series of in vitro knockdown and activation experiments were performed to establish the signaling pathway responsible for mechanics-induced MCs activation. In addition, an animal model of renal fibrosis was established in mice induced by unilateral ureteral occlusion (UUO). Lentiviral particles containing short hairpin RNA (sh RNA) targeting Piezo1 were used to explore the effect of Piezo1 knockdown on matrix stiffness-induced MCs activation and UUO-induced renal fibrosis. An in vitro experiment demonstrated that elevated ECM stiffness triggered the activation of Piezo1, which increased YAP nuclear translocation through the p38MAPK, and consequently led to increased ECM secretion. Furthermore, these consequences have been verified in the animal model of renal fibrosis induced by UUO and Piezo1 knockdown could alleviate UUO-induced fibrosis and improve renal function in vivo. Collectively, our results for the first time demonstrate enhanced matrix stiffness aggravates the progression of renal fibrosis through the Piezo1-p38MAPK-YAP pathway. Targeting mechanosensitive Piezo1 might be a potential therapeutic strategy for delaying the progression of renal fibrosis.